Integrating hemp in a replicable model for affordable, low carbon housing: a zero carbon microhome prototype for the Kansas Flint Hills - Gibson, Michael D. (Frontiers in Sustainability, 2025)
Homes in the U.S. account for a substantial share of energy use and emissions, while the shortage of affordable housing underscores the need for new design and construction approaches. The Zero Carbon Microhome, designed by architecture students in the Net Positive Studio at Kansas State University, demonstrates how hempcrete and hemp fiber can be integrated into a prototype for affordable infill housing that achieves both annual net zero energy and net zero carbon over its lifespan. Hemp’s use in the project is central to reducing embodied emissions in the structure and enclosure of the home. A carbon assessment incorporates emissions from the hempcrete and hemp fiber insulation to evaluate their role in achieving net zero carbon. An accompanying energy analysis examines the thermal properties of these materials and demonstrates how the project attains net zero energy, with operational carbon reduced and offset by renewable energy. The hempcrete mixture is detailed, along with factors influencing its performance. Together, these strategies offer a replicable model for applying hemp and hempcrete in the pursuit of affordable, net zero energy, net zero carbon housing.